Mental health protection in the social emergency: reflections and guidelines for mental health workers - Ibañez C., Carlos; Aguilera H., Pablo (Revista de Psiquiatría Clínica, 2021)
Emergency and disaster situations cause suffering and increase mental health problems in affected populations. There are national and international publications that provide strategies and guidelines to protect the mental health of population in these situations. The social outbreak that had place in Chile in October 2019 presents some peculiarities that make it necessary to review concepts and use them in a pragmatic way so us, health professionals, can collaborate not only to reduce discomfort and the consequences of events that have emotionally mobilized an entire country, but also as tools to deal with anxiety itself. In the article, the term Social Emergency is proposed to define more precisely the phenomenon. It is proposed the importance of identifying and combating Paranoid Anxiety as a mechanism that promotes violent polarization at the individual and collective level. Finally, some general recommendations are mentioned regarding strategies to protect the mental health of the population and specific recommendations regarding the role of mental health professionals in emergency situations.